A Generalized Analytical Solution for Preferential Infiltration and Wetting - Stewart, R.D. (2020)
The analysis revealed that infiltration partitioning varies with time, with flow regimes changing at time of ponding of the matrix and again at time of ponding in the macropores. The results also showed that the fraction of infiltration due to preferential flow increases as a function of rainfall and relative volume of the macropore domain. Conversely, macropore volume has an inverse relationship with wetting depth: all other factors being equal, infiltration due to preferential flow becomes proportionally greater than matrix infiltration as macropore volume decreases. Finally, the proposed infiltration and wetting equations were compared with numerical simulations of the Richards equation for dual‐permeability soils. The analytical solutions closely approximated the numerical results, with root mean square deviation values ≤0.15 and simulated wetting depths within 35% of one another, even as modeled times to ponding varied by 5 to 80%. Altogether, the theoretical framework developed in this study provides new insight into preferential flow dynamics during rainfall events.